1997
DOI: 10.1093/molehr/3.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in-situ hybridization and sequence-tagged sites for delineation of an X:Y translocation in a patient with secondary amenorrhoea

Abstract: We describe a phenotypically normal female with secondary amenorrhoea due to a translocation of genetic material involving the long arm of chromosome X (Xq28) and the long arm of chromosome Y (Yq11). We used fluorescent in situ hybridization to localize the breakpoint on the Xq. The Y chromosome breakpoint was identified using polymerase chain reaction (PCR) detection of sequence-tagged sites (STS) specific for interval 5 at Yq11.21. The relationship between this X:Y translocation and premature ovarian failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…These loci are located in Xq26-28 (POF1) and Xq13.3-q22 (POF2), respectively (Tharapel et al 1993;Powell et al 1994;Delon et al 1997;Sala et al 1997;Davison et al 1998;Davison et al 1999). Within the POF2 locus, a possible candidate gene for the POF condition has recently been identified (Bione et al 1998), and it represents the human homologue (DIAPH2) of the Drosophila melanogaster diaphanous gene, mutations of which affect oogenesis or spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These loci are located in Xq26-28 (POF1) and Xq13.3-q22 (POF2), respectively (Tharapel et al 1993;Powell et al 1994;Delon et al 1997;Sala et al 1997;Davison et al 1998;Davison et al 1999). Within the POF2 locus, a possible candidate gene for the POF condition has recently been identified (Bione et al 1998), and it represents the human homologue (DIAPH2) of the Drosophila melanogaster diaphanous gene, mutations of which affect oogenesis or spermatogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Then, with FISH and PCR methods, the fine breakpoints of the X and Y chromosomes were determined to be at Xq26.3 and Yq11.223, respectively. To our knowledge patients with POF and with a crypt Y chromosome fragment resulting from an Xq and Yq translocation are very rare, and only one case carrying a similar karyotype was reported by Delon et al (5). However, in that case, the derivative X chromosome was apparently longer than the normal X chromosome.…”
Section: Discussionmentioning
confidence: 80%
“…It seems that our patient was at a low risk for tumorigenesis. However, we noticed that Delon et al (5) reported a similar case with the karyotype 46,X,der(X)t(X;Y) (q28;q11.21), and a gonadectomy was recommended. Therefore, we explained the potential risk of malignant germ cell tumor development to the patient, but she refused prophylactic gonadectomy.…”
Section: Discussionmentioning
confidence: 96%
“…Xq and Yq interchanges are less frequent, and only a few cases of have been reported [2,3]. These reports described with twins as a result of a successful intrauterine insemination procedure, and the fetal ultrasound examination at 11 weeks of gestation revealed an increased risk for Down syndrome in one fetus based on nuchal translucency (NT) measurement (first fetus NT = 3.1 mm, second fetus NT = 1.3 mm).…”
Section: Introductionmentioning
confidence: 99%